2021
DOI: 10.1080/16506073.2020.1861084
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties with emotion regulation and drinking during the COVID-19 pandemic among undergraduates: the serial mediation of COVID-related distress and drinking to cope with the pandemic

Abstract: 2021): Difficulties with emotion regulation and drinking during the COVID-19 pandemic among undergraduates: the serial mediation of COVIDrelated distress and drinking to cope with the pandemic, Cognitive Behaviour Therapy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
16
2
1
Order By: Relevance
“…We found no longitudinal evidence on the effect of psychological distress on risky drinking during the COVID-19 pandemic. This finding contrasts previous findings on the role of psychological distress and mental well-being in drinking during the pandemic [ 9 , 14 - 18 ]. One potential reason for this might be that in global comparisons, the COVID-19 situation was manageable in Finland during 2020 and spring 2021.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found no longitudinal evidence on the effect of psychological distress on risky drinking during the COVID-19 pandemic. This finding contrasts previous findings on the role of psychological distress and mental well-being in drinking during the pandemic [ 9 , 14 - 18 ]. One potential reason for this might be that in global comparisons, the COVID-19 situation was manageable in Finland during 2020 and spring 2021.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus far, only a few studies have been based on longitudinal samples [ 1 , 6 , 7 , 12 , 13 ]. Additionally, it seems that individuals react to the COVID-19 crisis differently, and those facing emotional worry and distress are especially at risk for increased drinking [ 1 , 9 , 14 - 18 ]. There might be specific risk factors associated with increased drinking during the COVID-19 pandemic, and the role of social media in drinking, in particular, calls for attention.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of college students report that pandemic-related closures of college campuses have negatively impacted their mental health ( Active Minds, 2020 ; López-Castro et al, 2021 ; Oh et al, 2021 ). Recent authors have identified dramatic increases in alcohol use among college students as a coping mechanism during the COVID-19 pandemic ( Bonar et al, 2021 ; Buckner et al, 2021 ; Coakley et al, 2021 ; Jackson et al, 2021 ). A quarter of college students surveyed by the American College Health Association during Fall 2020 scored >13 on the Kessler 6 Non-Specific Psychological Distress Scale, which is consistent with significant impairment in life activities due to severe mental illness ( American College Health Association, 2020 ).…”
mentioning
confidence: 99%
“…Extreme drinking among students is known to be associated with social, enhancement and coping motives ( White et al, 2016 ). Loneliness, difficulty with goal-directed behavior, COVID-19-related worry and reading COVID-19-related news have been associated with drinking to cope with the pandemic ( Buckner et al, 2021 ; Mohr et al, 2021 ). There is also evidence that increased drinking during the COVID-19 pandemic has been more common among people with symptoms of anxiety and depression ( Tran et al, 2020 ; Lechner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%